Vliv clodronátu na kostní denzitu pacientů s mnohocetným myelomem--dvouleté sledování lécebného úcinku - Adam, Z; Prokes, B; Znojĭl, V; Vorlícek, J; Hejlová, N; Hájek, D; Krejcí, M (Vnitrni lekarstvi, 1996)
Biphosphonates are used for the treatment of hypercalcaemia as well as in normocalcaemic patients for the long-term inhibition of malignant osteolytic bone processes. In patients with multiple myelomas treated with biphosphonates in randomized studies a reduction of the number of new osteolytic foci was proved and improvement of the quality of life. The objective of the present study was to evaluate the effect of clodronat on the development of bone density in patients with multiple myeloma. In the study since 1993 27 patients were included. In August 1995 22 patients were evaluated who were treated for more than 12 months with clodronat (Bonefos Leiras). The patients were given clodronat in i.v. infusions (five infusions à 600 mg) in three-month intervals. After six-month intervals the amount of hydroxyapatite in the lumbar vertebrae was evaluated by CT densitometry. Statistical testing of trends of assessed bone density values revealed that not even after two years of the disease a statistically significant reduction of the bone density occurs. Treatment was very well tolerated, gastrointestinal problems were an exception. At the onset of the investigation three patients had symptoms of mild tetany, and a decline of the calcaemia below normal values was recorded. As soon as regular administration of calcium preparations was started during clodronat administration, the calcaemia did not decline below normal levels and enhanced neuromuscular irritability did not develop. Clodronat stabilizes the amount of bone mass, reduces pain and also improves the quality of the patients life. It should be included among standard treatment of patients with multiple myeloma.
Keywords: Follow-Up Studies; Bone Density; Clodronic Acid; Humans; lidé; následné studie; Diphosphonates; hyperkalcemie; lidé středního věku; Middle Aged; Multiple Myeloma; kostní denzita; Female; Male; Adult; mnohočetný myelom; dichlormethylendifosfonát; mužské pohlaví; Aged; ženské pohlaví; Osteolysis; dospělí; bisfosfonáty; Hypercalcemia; osteolýza; senioři